Metti in circolo il colore: Un’esperienza di didattica integrata tra chimica e rappresentazioni grafiche - Palazzi, Sergio (Chimica nella Scuola, 2025)
Positive interactions between different teaching areas are always sought, but not so often found. This work describes a fortuitous but effective cooperation of scientific and artistic disciplines, in a 2nd year class of a Graphical Technical Institute. Ordinary routine gouache painted paper samples have been examined in a scientific way. Their colours have been measured with a spectrophotometer and then projected in some different colour spaces, with simple 2D and 3D visualizations that changed the students’ opinions on some artistic cliches like “colour wheels” or “primary colours”. At the same time, chemical, safety and sustainability themes have been introduced by searching the nature and behaviours of pigments and dyestuffs in commercial products. Some new ideas have been collected and transferred to the more technically oriented students of the courses on Textile Design and Finishing technologies (“Sistema Moda”)